Developing an Artificial Intelligence-Based Learning Model to Enhance Students’ Critical Thinking Skills in Elementary Education - Achmad Sumali; Fathur Rokhman; Wagiran Wagiran (Universitas Negeri Semarang, 2026)
The rapid development of artificial intelligence (AI) technology has opened new opportunities in reforming educational paradigms, particularly in elementary schools. However, the integration of AI-based learning models specifically designed to enhance critical thinking skills at the elementary level remains limited. This study aims to develop and evaluate an AI-based learning model that systematically cultivates critical thinking competencies among elementary school students. A research and development (R&D) approach following the ADDIE model (Analysis, Design, Development, Implementation, Evaluation) was employed. Participants consisted of 120 fourth-grade students from three public elementary schools in Tangerang Selatan, Indonesia, selected through purposive sampling. Data were collected using critical thinking assessment rubrics, learning observation sheets, and student response questionnaires. Validity was established through expert review panels, while reliability was confirmed through Cronbach’s Alpha analysis. Findings revealed that the AI-based learning model demonstrated high validity (mean score 4.32/5.00), strong practicality (86.7%), and significant effectiveness in improving students’ critical thinking skills, with a mean post-test score of 82.4 compared to 61.3 in the pre-test (N-gain = 0.54, categorized as moderate). Students showed particularly notable improvement in the dimensions of analysis, evaluation, and inference. This study contributes an innovative, evidence-based learning model that can be adapted to diverse elementary education contexts and advocates for broader AI integration in primary education curricula.